Welfare against growth gains in post-transition countries: What are the consequences for stability? - Maria Lissowska (Kiel Institute for the World Economy (IfW), 2012)
This paper discusses the underpinnings of the financial crisis of the last decade. It explores the endogenous reasons of this crisis, and in particular a possible link between delayed and unequal growth of household incomes in post-transition countries on one hand and the instability of their growth and depth of recession after the financial crisis on the other. It indicates possible microeconomic factors under-pinning rapidly growing indebtedness of households, enabling faster consumption growth, but subject to fluctuations. It claims also that artificially boosted growth of consumption and a favourable proportion between wages and profits could attract investment (also FDI), possibly searching for short-term gains. It underlines that the inflow of financial funds contributed to, but did not cause instability growth in this region.
Keywords: I38; J48; P51; 330; Welfare; labour market; post-transition economies; stability